Child Care Choices by Italian Households - Daniela Del Boca; Marilena Locatelli; Daniela Vuri (Institute for the Study of Labor (IZA), 2004)
In spite of relatively generous public subsidies and a reputation for high quality, only a very limited proportion of Italian families use public child care. In this paper we explore the significance of various factors on the choices made between different types of child care. In part one, we use a simulation exercise to show the impact of cost and availability on child care choices. In part two, we present the results of an explorative econometric analysis using a matched data set for 1998 from the Bank of Italy (SHIW) and ISTAT Multiscopo. We find evidence that factors related to family composition and support as well as to the characteristics of child care are important in explaining the choices made by Italian families. Assistance provided by grandmothers and husbands appears to be of crucial significance to Italian mothers who are seeking to reconcile the difficulties stemming from the rigidity of the labor market and the limitations of child care. Rationing, both of public and private child care, also proves to be an important factor affecting households? choices. An understanding of the importance of these factors is relevant in the evaluation of social policies encouraging mothers? participation in the labor market in Italy.
Keywords: J2; D1; C3; 330; labor market decisions; child care; Kinderbetreuung; Haushaltsökonomik; Frauenerwerbstätigkeit; Arbeitsangebot; Italien